The Long-Run Economic Consequences of Iodine Supplementation - Daniel Araújo; Bladimir Carrillo; Breno Sampaio (Institute of Labor Economics (IZA), 2021)
We present evidence on the impacts of a large-scale iodine supplementation program in Tanzania on individuals' long-term economic outcomes. Exploiting the timing and location of the intervention, we document that in utero exposure to the program increased completed years of education and income scores in adulthood. We find no increase in total employment, but a significant change in the occupational structure. Cohorts exposed to the program are less likely to work in agricultural self-employment and more likely to hold skilled jobs that typically demand higher levels of education. Together, these results demonstrate that iodine deficiency can have long-run implications for occupational choices and labor market incomes in low-income regions.
Keywords: I15; I18; J24; N35; 330; educational attainment; long-run; iodine supplementation; labor market outcomes